Studi Seismik Tomografi Waktu Tempuh Untuk Identifikasi Zona Lemah dengan Menggunakan Konsep Ray Tracing Berdasarkan Algoritma Dijkstra - Wiji Raharjo; Indriati Retno Palupi; Intan Paramita Haty (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
Tomography is a popular method in describing the subsurface based on P and S waves parameter of the seismic wave. It can show the low velocity zone or the weak zone that usually associated with the structure or fluid evidence. However, it needs some informations about the hypocenter and stations location, and the initial velocity model as the geological model. Based on the information, then ray path on each grid/block in the research area is calculated along from the hypocenter to the each station. Ray path concept is based on the Snell Law, Fermat and Hyugens principle where the wave will be dispersioned when it faces to the different medium and it will choose the medium with the fastest travel time. Then by the inversion process, the tomogram can be resulted. Dijkstra Algorithm is choosen as the basic mathematical equation for the ray path calculation because it is easy and use in some digital platform. This algorithm is provened can result the good tomogram where it can be showed the structure of the geological model.